AN ANALYSIS OF ENGLISH CODE MIXING USED BY MAIN CHARACTER IN KAGET NIKAH FILM - Yasinta Trililis Anjelina Maduwu; Devi Tri Romadhoni; Syafrianto SM (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2023)
The phenomenon of code mixing is often used in communication. In this case, people sometimes mix language into other languages to gain understanding and communication success. The purpose of this study is to determine the type of insertion in code mixing used in the film "Kaget Nikah". In this study, researchers focused on Indonesian and English utterances. This research method uses a descriptive qualitative method. It describes research results that are objectively analyzed by collecting data. The data source is a film script. Researchers use the free listening method. The results are displayed in the code mixing table and explained in narrative text. The researcher uses 25 data from utterances in the film which are considered capable of representing code-mixing. There are 15 word levels, 5 phrase levels, 2 clause levels, 1 idiom level, 1 hybrid level and 1 word repetition level.